Unveiling the heterogeneous impacts of environmental taxes on energy consumption and energy intensity: Empirical evidence from OECD countries. (1st July 2021) - Bashir, Muhammad Farhan; MA, Benjiang; Shahbaz, Muhammad; Shahzad, Umer; Vo, Xuan Vinh
Abstract: This study sheds new light on the ambiguous role of environmental taxes in reducing energy usage and energy intensity from 1994 to 2018. We contribute to the energy economics literature by unveiling the interaction between environmental taxes, energy intensity, and energy consumption in 29 OECD economies. Owing to the recent environmental reforms and focus on SDGs, it is necessary to examine the impact of environmental taxes on energy consumption and energy efficiency function. The empirical results from FMOLS, DOLS, and panel quantile regression reveal that the implementation of environmental tax helps to control overall energy usage and promotes energy efficiency by encouraging policymakers, industries, and residents to promote innovation in environment related technologies. We conclude by arguing that the efforts towards a sustainable environment by reducing energy consumption should adopt innovative policies by ensuring the displacement of non-renewables and improve energy efficiency.